2023
DOI: 10.3390/polym15061404
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidized and Maleinized Hemp Oil to Develop Fully Bio-Based Epoxy Resin Based on Anhydride Hardeners

Abstract: The present work aims to develop thermosetting resins using epoxidized hemp oil (EHO) as a bio-based epoxy matrix and a mixture of methyl nadic anhydride (MNA) and maleinized hemp oil (MHO) in different ratios as hardeners. The results show that the mixture with only MNA as a hardener is characterized by high stiffness and brittleness. In addition, this material is characterized by a high curing time of around 170 min. On the other hand, as the MHO content in the resin increases, the mechanical strength proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The samples composed of commercial epoxy and EHO exhibited superior flexural performance. However, it was observed that the maximum bio content (40%) exhibited inferior performance in flexural properties, both in comparison to the hemp-based epoxy thermoset outlined in Lerma-Canto et al’s study [ 64 ] and the conventional epoxy thermoset (refer to Table 12 ). Beyond 30% bio content, there was a significant reduction in the crosslinking density, resulting in a notable decline in the mechanical properties of the epoxy.…”
Section: Bio-epoxy Resinsmentioning
confidence: 88%
See 3 more Smart Citations
“…The samples composed of commercial epoxy and EHO exhibited superior flexural performance. However, it was observed that the maximum bio content (40%) exhibited inferior performance in flexural properties, both in comparison to the hemp-based epoxy thermoset outlined in Lerma-Canto et al’s study [ 64 ] and the conventional epoxy thermoset (refer to Table 12 ). Beyond 30% bio content, there was a significant reduction in the crosslinking density, resulting in a notable decline in the mechanical properties of the epoxy.…”
Section: Bio-epoxy Resinsmentioning
confidence: 88%
“…Epoxidation reaction also offers a possible pathway for incorporating natural oils into bio-epoxy resin formulations. Among edible oils, options such as soybean [ 56 , 57 , 58 , 59 , 60 ], linseed [ 59 , 61 , 62 , 63 ] and hemp [ 60 , 64 , 65 ], stand out as potential sources for developing environmentally sustainable epoxy systems, as extensively analyzed in the comprehensive overview by Mustapha et al [ 66 ]. From triglyceride vegetable oils, such as coconut, soybean or palm oil, it is possible to obtain the glycerol , which is also commercially used to produce commercial resins [ 67 , 68 , 69 ] and proposed in the literature for the synthesis of new epoxy systems [ 38 , 70 , 71 ].…”
Section: Bio-epoxy Resinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to high mechanical strength, good adhesiveness, low cost, high thermal stability, good chemical resistance, and ease of use of epoxy resins, they are successfully used in load-bearing applications (aerospace, automotive, construction, and marine). In addition, they are also utilized in the production of coatings, adhesives, insulation, and high-performance composites [4,[12][13][14][15][16]. However, due to the insolubility and non-fusibility of epoxy resins, they are difficult to recycle, which results in a waste of resources and limits their applications [17].…”
Section: Introductionmentioning
confidence: 99%